Word of Mouth dan Media Sosial terhadap Minat Beli Konsumen pada Kafe Kenalin Ini Kopi di Universitas Buana Perjuangan Karawang - Nopri Hardianto; N.Neni Triana; Thomas Nadeak (Journal of Management and Bussines (JOMB), 2024)
This research aims to test and analyze the influence of word of mouth and social media on consumer purchasing interest at the "Kenalin Ini Kopi" cafe. The research method used is quantitative by applying descriptive verification analysis. Research data sources involve the collection of secondary and primary data. The sample for this research was 100 students from Buana Perjuangan University, Karawang, who were selected using a purposive sampling technique. The research results show that word of mouth supported by social media promotions has a significant effect on consumer purchasing interest at the "Kenalin Ini Kopi" cafe. The implication of these findings is that the "Know This Coffee" cafe can improve their promotional strategy by collaborating with influencers and creating interesting videographic content to reach consumers more widely. In conclusion, this research contributes to understanding the influence of word of mouth and social media in increasing consumer buying interest in the coffee shop industry. As a result, "Know This Coffee" cafes and similar stakeholders can optimize their marketing strategies to achieve greater success in an increasingly. Keywords: Social Media, Purchase Interest, Word of Mouth